Theoretical investigations on molecules - Nilar, S.H.M. (My University, 1980)
The research presented in this thesis can be broadly classified into four categories. The first category involves semi-empirical molecular orbital calculations on pi electron systems. A semi-empirical molecular orbital method for pi systems is developed and used to study molecular properties like ionisation Potential, electronic spectra, charge density, bond order distributions and gradation of ...